Here, there and everywhere: emotion and mental state talk in different social contexts predicts empathic helping in toddlers - Drummond, Jesse; Paul, Elena F.; Waugh, Whitney E.; Hammond, Stuart I.; Brownell, Celia A. (Frontiers in Psychology, 2014)
A growing body of literature suggests that parents socialize early-emerging prosocial behavior across varied contexts and in subtle yet powerful ways. We focus on discourse about emotions and mental states as one potential socialization mechanism given its conceptual relevance to prosocial behavior and its known positive relations with emotion understanding and social-cognitive development, as well as parents’ frequent use of such discourse beginning in infancy. Specifically, we ask how parents’ emotion and mental state talk with their toddlers relates to toddlers’ helping and how these associations vary by context. Children aged 18- to 30-months (n=38) interacted with a parent during book reading and joint play with toys, two everyday contexts that afford parental discussion of emotions and mental states. Children also participated in instrumental and empathic helping tasks. Results revealed that although parents discuss mental states with their children in both contexts, the nature of their talk differs: during book reading parents labeled emotions and mental states significantly more often than during joint play, especially simple affect words (e.g. happy, sad) and explanations or elaborations of emotions; whereas they used more desire talk and mental state words (e.g. think, know) in joint play. Parents’ emotion and mental state discourse related to children’s empathic, emotion-based helping behavior; however, it did not relate to instrumental, action-based helping. Moreover, relations between parent talk and empathic helping varied by context: children who helped more quickly had parents who labeled emotion and mental states more often during joint play and who elicited this talk more often during book reading. As emotion and mental state talk both varies between contexts and exhibits context-specific associations with empathic prosocial behavior early in development, we conclude that such discourse may be a key form of socialization in emerging prosociality.